Junior-Senior farewell ceremony - Gordon, John C. (photographer):::Creator::::::::::::
Possible Junior-Senior farewell ceremony. In the quad, women dressed in classical Greek-inspired gowns stand in a semicircle. A crowned woman stands in the center. On the left, right, and center front, three women holding buisines to their lips.